PENINGKATAN KEMAMPUAN MENYUSUI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS KOTABUMI II - Aryanti Wardiyah; Rina Puspitasari; Neta Susmarini (Universitas Malahayati Lampung, 2019)
ABSTRACT : INCREASING BREASTFEEDING AT PUBLIC HEALTH SERVICES (PUSKESMAS KOTABUMI II) Background : Breastfeeding is role of a mother after delivering of baby. Based of pre-survey data from 2015 to 2016 at Public Health Services (Puskesmas Kotabumi II) recorded the postpartum had been increased from 9,41% to 14,6 % while at Kotabumi II Public Health Center of although with lowest coverage but decreased coverge from year 2015 to in 2016 from 35,7% to 21,3%. Based on data from Kotabumi II Public Health Center troughout 2017 it is known 144 post partum mothers who exclusively breastfed only 19,4%.Puspose: Knowed effectively postpartum positioning and attachement education for increasing breastfeeding at Public Health Services (puskesmas Kotabumi II) North Lampung 20018.Methods : This research was quantitative research, Quasi experimental design. The research conducted on postpartum as many as 34 respondents. Sampling technique used accidental sampling. Data collected by observation sheets. Data analysis performed univariate (mean) and bivariate (t test).Results : Found in the study, the ability of breastfeeding in postpartum before giving health education with a mean value of 57.06 and standard deviation of 11.284 and after giving health education with a mean of 86.59 and standard deviation of 7.427.Conclusion : There is influence of health education to improve the ability of breastfeeding of post partum at Public Health Services (Puskesmas) Kotabumi II North Lampung in 2018. It is expected that health care provider to be an active role in giving information or health information in breastfeeding related to mother's knowledge and behavior in breastfeeding toward baby, follow-up such as periodic evaluation, so that the purpose of breastfeeding is achieved. Keywords: Postpartum, Positioning, Attachment Education, Increasing Breastfeeding INTISARI: PENINGKATAN KEMAMPUAN MENYUSUI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS KOTABUMI II Pendahuluan : Memberikan ASI merupakan tugas seorang ibu setelah tugas melahirkan bayi berhasil dilaluinya. Berdasarkan prasurvey di Puskesmas Kotabumi II pada ibu yang kontrol prenatal care di dapat yang masih memberikan air susu ibu (ASI) dari 10 ibu didapatkan 6 (60%) yang tidak memberikan ASI.Tujuan : Diketahui pengaruh pendidikan kesehatan teradap kemampuan menyusui terhadap pada ibu post partum di Wilayah Kerja Puskesmas Kotabumi II Kabupaten Lampung Utara tahun 2018.Metode : Penelitian ini penelitian kuantitatif, rancangan Quasi Eksperimen. Penelitian telah dilakukan bulan Februari-Maret 2018 di Wilayah Kerja Puskesmas Kotabumi II Kabupaten Lampung Utara tahun 2018. Populasi penelitian ibu post partum, berdasarkan ibu hamil trimester 3 atau yang akan bersalin dalam 3 bulan kedepan (Januari-Maret) sebanyak 98 orang, sampel 30 orang. Teknik Pengambilan sampel accidental sampling. Pengumpulan data menggunakan lembar observasi. Analisis data secara univariat dan bivariat (Uji t).Hasil : Didapatkan dalam penelitian ini, kemampuan menyusui pada ibu postpartum sebelum diberikan pendidikan kesehatan dengan nilai mean 57,06 dan standar deviasi 11,284 dan setelah diberikan pendidikan kesehatan dengan nilai mean 86,59 dan standar deviasi 7,427.Simpulan : Ada pengaruh pengaruh pendidikan kesehatan terhadap peningkatan kemampuan menyusui ibu post partum di Wilayah Kerja Puskesmas Kotabumi II Kabupaten Lampung Utara tahun 2018. Diharapkan petugas kesehatan lebih berperan aktif memberikan penyuluhan atau informasi kesehatan terhadap ibu menyusui terkait dengan pengetahuan dan perilaku menyusui ibu terhadap bayi, serta diadakan tindak lanjut misalnya evaluasi periodik, agar tujuan dari menyusui tercapai. Kata kunci : Pendidikan kesehatan, tehnik menyusui, kemampuan menyusui, Ibu post partum